Revisiting McCutchen’s Teaching Dance as Art in Education: Bridging Embodied Learning and Digital Archives - Rivaldi Indra Hapidzin; Juju Masunah; Trianti Nugraheni; Ayo Sunaryo (Journal of General Education and Humanities, 2026)
This article critically reviews Brenda Pugh McCutchen’s Teaching Dance as Art in Education (2006) to recontextualize its pedagogical framework within discussions of embodied learning, ethnopedagogy, and digital archives. Using a qualitative critical book review approach, the study examines the book’s four cornerstones: Dancing and Performing; Creating and Composing; Knowing History, Culture, and Context; and Analyzing and Critiquing. The review finds that McCutchen’s framework remains pedagogically relevant because it integrates embodied practice, creativity, cultural understanding, and critical reflection. However, it also reveals limitations, particularly its Euro-American orientation, limited ethnopedagogical perspective, and lack of attention to digital technologies. To address these gaps, the article proposes a conceptual extension that links embodied learning with digital archives as complementary tools for documentation, preservation, accessibility, and cultural transmission. While digital archives cannot replace lived bodily experience, their integration with McCutchen’s framework may strengthen dance education by supporting preservation and critical engagement with dance knowledge. As a conceptual study based on a single primary text and selected literature, this review does not include empirical data or practical implementation. Nevertheless, it suggests that combining embodied learning and digital archives offers a valuable direction for dance education in the digital era.